Agronomic biofortification of basmati rice (Oryza sativa L.) through iron and boron under varying seedling densities - Rajput, Pradeep; Singh, Adesh; Rajput, Ravindra Kumar; Bhatt, Rajan; Alamri, Saud; Kanaujiya, Pradeep Kr.; Gautam, Sandip Kumar (Frontiers in Sustainable Food Systems, 2024)
At present, we have adequate production of rice to fulfill the needs of humans. Now it is time to produce biofortified rice, whose grains contain enough amounts of nutrients like iron and boron. Two field experiments were carried out in Kharif 2019 and 2020 at Meerut (Uttar Pradesh), India, to find the effect of iron and boron nutrition on rice with different planting densities. The main plot treatment consists of three planting densities, and the subplot treatment consists of five foliar applications of micronutrients. They were tested in a split-plot design (SPD) with three replications. The results revealed that the rice transplanted with one seedling/hill gave the highest iron and boron content in grains and/or the crop fortified with iron and boron at 0.1 and 0.04% applied at the maximum tillering (MT) and panicle initiation (PI) stages of rice, respectively. The higher values of yield-contributing characters such as effective tillers/m2, panicle length (cm), grain weight/panicle (g), and test weight (g), as well as quality parameters such as nutrient content in grain (mg/kg), volume expansion ratio, protein content in grains (%), and amylose content (%) of rice were noticed in one seedling/hill except effective tillers/m2 during the first and second years. Application of Fe and B at the MT and PI stages of rice improved almost all the yield attributes and quality parameters. Planting density of two and three seedlings/hill was recorded at par values of grain yield, followed by one seedling/hill. Rice transplanted with three seedlings/hill obtained an average of 10.1 and 10.6% more grain yield than one seedling/hill during the first and second years, respectively. However, the application of Fe at 0.1% and B at 0.04% during both stages through foliar spray resulted in the highest seed yield and showed parity with the application of iron at 0.1% at the MT stage and boron at 0.04% at the PI stage. Economics revealed that the planting density of three seedlings/hill gave the maximum net returns of 61,585 and 66,752 ₹/ha with a benefit–cost ratio of 2.12 and 2.19 during 2019 and 2020, respectively. Furthermore, the highest net returns (62,188 and 67,938 ₹/ha) and benefit–cost ratio (2.15 and 2.23) were observed from the treatment of iron at 0.1% and boron at 0.04% at the MT and PI stages during the first and second years, respectively.